Real Estate Transactions Related to Investment in Algerian Legislation - Benyattou, Djemli; Belouadah, Tayeb (Journal of Legal Studies and Researches, 2024)
In order to optimally exploit the lands belonging to the state’s private property, the state carries out a group of real estate transactions. The lands belonging to the state’s private property are granted according to their legal nature and according to the type of activity desired. In this article, we will discuss the mechanisms for granting industrial real estate and agricultural lands.